Study on the critical behavior and magnetocaloric effect of RCrO3 (R = Gd, Dy). Issue 8 (15th April 2023) - Wang, Qingwei; Lv, Bowen; Wu, Qiong; Hu, Xiukun; Luo, Xinyao; Fang, Jieyang; Yu, Nengjun; Yang, Hangfu; Pan, Minxiang; Ge, Hongliang
Abstract: In this study, we aim to examine the critical behavior and magnetocaloric effect of RCrO3 (R = Gd, Dy) polycrystal synthesized by solid-state sintering. As per the heat capacity fitting curves, GdCrO3 and DyCrO3 fit the 3D-XY and 3D-Ising models, respectively. The analysis of heat capacity curves, field cooling (FC), and zero-field cooling (ZFC) curves reveals two magnetic phase transitions in the samples, with TN Cr  = 174 K, TN Gd  = 3.7 K and TN Cr  = 152 K, TN Dy  = 3.5 K for GdCrO3 and DyCrO3, respectively. Under a 50 kOe magnetic field, the maximum magnetic entropy change (−ΔSm max ) and relative cooling efficiency (RCP) of the sample are 39.9 J/kg K, 373.4 J/kg and 15.9 J/kg K, 276 J/kg for the two samples, respectively. We believe that the significant magnetocaloric effect of GdCrO3 is associated with its critical behavior. This provides an additional reference for the origin of the large magnetocaloric effect of materials.